Epidemiologic and clinical characteristics of neonates with late-onset COVID-19: 1-year data of Turkish Neonatal Society - Bulbul, Ali; Ozdemir, Ozmert Ma; Tayman C.; Oncel M.Y.; Imdadoglu T.; Dilek M.; Yaman A.; Narter, Fatma; Er, Ilkay; Kahveci, Hasan; Erdeve, Omer; Koc, Esin; et al. (Springer Science and Business Media LLC, 2022)
The literature on neonates with SARS-CoV-2 is mainly concerned with perinatal cases, and scanty data are available about environmentally infected neonates. To fill knowledge gaps on the course and prognosis of neonatal cases, we analyzed 1-year data from the Turkish Neonatal Society in this prospective cohort study of neonates with postnatal transmission. Data from 44 neonatal intensive care units (NICUs), of neonates with positive RT-PCR results at days 5-28 of life, were extracted from the online registry system and analyzed. Of 176 cases, most were term infants with normal birth weight. Fever was the most common symptom (64.2%), followed by feeding intolerance (25.6%), and cough (21.6%). The median length of hospitalization was 9 days, with approximately one quarter of infants receiving some type of ventilatory support. Myocarditis (5.7%) was the most common complication during follow-up. Among the clinical findings, cough (odds ratio [OR]: 9.52, 95% confidence interval [CI]: 4.17-21.71), tachypnea (OR: 26.5, 95% CI: 9.59-73.19), and chest retractions (OR: 27.5, 95% CI: 5.96-126.96) were associated with more severe clinical disease. Also, there were significant differences in the C-reactive protein level, prothrombin time (PT), partial thromboplastin time, international normalized ratio, and days in the NICU (p = 0.002, p = 0.012, p = 0.034, p = 0.008, and p < 0.001, respectively) between patients with mild-moderate and severe-critical presentations. A PT above 14 s was a significant predictor of severe/critical cases, with a sensitivity of 64% and specificity of 73%.Our data showed that late-onset COVID-19 infection in neonates who need hospitalization can be severe, showing associations with high rates of ventilatory support and myocarditis. Cough, tachypnea, and retractions on admission suggest a severe disease course.ClinicalTrials.gov identifier: NCT04401540.• Neonatal cases of COVID-19 infection are mainly reported as perinatal COVID-19 cases. • Neonates with perinatal transmission have a mild course and favorable prognosis.• Among symptomatic neonates with late-onset COVID-19 infection, fever was the most common symptom, and almost one quarter of hospitalized cases needed some type of respiratory support. Myocarditis was the most common complication. • The presence of cough, tachypnea, retractions, and a PT above 14 s were associated with an increased risk of severe COVID-19.
Keywords: multiple organ failure; vancomycin; epidemiological data; diarrhea; oxygen therapy; rash; assisted ventilation; computer assisted tomography; somnolence; newborn; partial thromboplastin time; Pregnancy; Severe acute respiratory syndrome coronavirus 2; Prospective Studies; Pregnancy Complications, Infectious; azithromycin; fever; Tachypnea; C reactive protein; disseminated intravascular clotting; artificial ventilation; carbapenem derivative; cohort analysis; Management; Myocarditis; female; rhinorrhea; breast feeding; mother to child transmission; real time polymerase chain reaction; artificial milk; epidemiology; Original Article; Female; pregnancy; hospitalization; prospective study; lung consolidation; oseltamivir; SARS-Cov-2; COVID-19 testing; gentamicin; Article; coronavirus disease 2019; male; ground glass opacity; follow up; Humans; controlled study; irritability; human; coughing; protein expression; SARS-CoV-2; cephalosporin derivative; Infant, Newborn; birth weight; COVID-19; Infant; Newborn; major clinical study; neonatal intensive care unit; prothrombin time; infant; Infectious Disease Transmission, Vertical; clinical feature; Postnatal; Cough; ampicillin; vertical transmission; pregnancy complication; myocarditis; newborn infection; continuous positive airway pressure; tachypnea; 2. Zero hunger; 3. Good health